Synthesis of benzoxazine-bridged porous composite materials based on Mannich reaction and preparation method and application thereof
Benzoxazine-bridged porous composite materials (M-COPs) synthesized through Mannich reaction solves the problems of long preparation time and insufficient antibacterial rate of existing porphyrin antibacterial materials, and achieves high efficiency for Gram-negative bacteria Inhibition and biocompatibility provide new photothermal conversion and antibacterial applications.
Patent Information
- Application Number
- CN202411349196.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The existing porphyrin antibacterial materials have a long preparation time and low yield, and the antibacterial rate of Gram-negative bacteria is insufficient, and the antibacterial rate of Gram-positive bacteria is relatively high, making it difficult to meet the gram-negative bacteria. Effective treatment needs.
The Mannich reaction was used to synthesize benzoxazine-bridged porous composites (M-COPs), prepared by one-pot method using hydroquinone, porphyrin and formaldehyde. As a solvent, no catalyst is required, the preparation process is simplified and yields are improved.
It achieves efficient inhibition of Gram-negative bacteria, reduces preparation costs, has high biocompatibility of materials, has little impact on 3T3 cells, and can catalyze the production of singlet oxygen in oxygen, which significantly improves the photothermal conversion effect and antibacterial performance.
Smart Images

Figure CN118878772B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomedicine technology, and in particular to a porous composite material based on the synthesis of benzoxazine bridges by Mannich reaction, and a preparation method and application thereof. Background Art
[0002] As a typical Gram-negative bacterium (G-), E. coli can be released into the surrounding environment through fecal deposition. Therefore, E. coli is widely excreted in water and soil, inevitably causing the occurrence of waterborne and foodborne diseases. Unlike Gram-positive bacteria (G+), G- bacteria have a more complex cell wall structure and are more tolerant to multiple therapies. In order to achieve the desired therapeutic effect, a large amount of therapeutic drugs is usually required, which not only increases the cost of treatment but also leads to the emergence of drug resistance. The development of highly efficient and specific therapeutic agents to eradicate E. coli without causing secondary pollution has become a new direction for the development of drugs to inhibit E. coli.
[0003] With the development of biomedical technology, phototherapy, including photothermal therapy (PTT) and photodynamic therapy (PDT), has become a fast and effective way to fight bacterial infections. As an accurate and non-invasive treatment option, phototherapy uses light as a drug with the help of photosensitizers (PS), which rarely induce drug resistance. However, the practical application of phototherapy technology also brings some challenges, including selectivity and specificity caused by the characteristics of light, which will act indiscriminately on various bacteria. At the same time, researchers' reports found that single-mode phototherapy is difficult to eradicate bacterial species. Therefore, there is an urgent need for a new photosensitizer that can not only play a combined therapeutic role but also impart photoelectric selectivity and specificity. Photothermal therapy affects the normal physiological response of bacteria by generating local high heat to destroy the protein structure of bacteria, causing irreversible damage to bacteria. However, photothermal anti-tumor and anti-infection requires higher temperatures, which causes thermal damage to normal tissues and limits its clinical application. Therefore, it is often used in combination with other treatments to reduce the side effects of photothermal therapy.
[0004] At present, researchers have discovered a variety of antibacterial drugs with phototherapy effects. Porphyrin is a type of macromolecular heterocyclic compound formed by interconnecting the α-carbon atoms of four pyrrole subunits through a methyl bridge (=CH-). At present, there are more and more reports on the preparation of bactericidal materials using porphyrin as raw material. These antibacterial drugs containing porphyrin are basically multipolymers, and the preparation time is very long. For example, the patent with application number CN202311630514.0 discloses a porphyrin microporous composite material based on β-cyclodextrin terephthalaldehyde inclusion complex, its preparation method and application, and the patent with application number CN202311021459.5 discloses a multifunctional cationic covalent organic framework material and its application. The above are all multipolymers containing porphyrin, but the preparation time takes at least 2 to 3 days, and the yield needs to be improved. In addition, in addition to the long preparation time and low yield, this type of multi-polymer antibacterial material has a common problem that the inhibition rate of Gram-positive bacteria is higher than that of Gram-negative bacteria, and Gram-negative bacteria are widely present in our living environment, and the inhibition rate of Gram-negative bacteria needs to be improved. Therefore, a porphyrin multi-polymer with a simple preparation method, short preparation time, high yield, and better ability to inhibit Gram-negative bacteria is needed to replace antibiotic therapeutic agents. Summary of the invention
[0005] In view of the above-mentioned prior art, the purpose of the present invention is to provide a porous composite material based on the Mannich reaction to synthesize benzoxazine bridges, and a preparation method and application thereof. The present invention uses hydroquinone, porphyrin and formaldehyde as structural units to prepare a porous composite material (M-COPs) based on the Mannich reaction to synthesize benzoxazine bridges. The method does not require a catalyst, has a short preparation time and a high yield, and can better inhibit Gram-negative bacteria, providing a new idea for multi-platform combined therapy.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] In a first aspect of the present invention, a method for preparing a porous composite material of benzoxazine bridges synthesized based on a Mannich reaction is provided, wherein:
[0008] Add polyhydroxyphenol, 5,10,15,20-tetrakis(4-aminophenyl)-porphyrin and formaldehyde to 1,4-dioxane, heat and stir, cool and filter to obtain a black solid, wash and dry to obtain a benzoxazine-bridged porous composite material;
[0009] The polyhydroxyphenol is hydroquinone;
[0010] The ratio of the added amounts of hydroquinone, 5,10,15,20-tetrakis(4-aminophenyl)porphyrin, formaldehyde and 1,4-dioxane is 20 mmol:5 mmol:80 mmol:70 mL.
[0011] Preferably, the heating and stirring temperature is 100° C., and the heating and stirring time is 4 to 8 hours.
[0012] Preferably, the 5,10,15,20-tetrakis(4-aminophenyl)-porphyrin is prepared by the following method:
[0013] (1) p-nitrobenzaldehyde, acetic anhydride and propionic acid are mixed and heated, and then pyrrole is added, refluxed, cooled to room temperature, filtered to obtain a precipitate, washed and dried to obtain 5,10,15,20-tetrakis(4-nitrophenyl)porphyrin;
[0014] (2) Mix 5,10,15,20-tetrakis(4-nitrophenyl)porphyrin, sodium sulfide nonahydrate and ammonium chloride, add N,N-dimethylformamide and distilled water under argon protection to react, cool and add distilled water dropwise, and after the addition is complete, cool, filter, wash and dry to obtain a dark purple solid, which is 10,15,20-tetrakis(4-aminophenyl)porphyrin.
[0015] The second aspect of the present invention provides a benzoxazine-bridged porous composite material (M-COPs) obtained by the above preparation method.
[0016] The third aspect of the present invention provides the use of a benzoxazine-bridged porous composite material in the preparation of an antibacterial drug or in the preparation of a product for improving the inhibition rate of Gram-negative bacteria.
[0017] Beneficial effects of the present invention:
[0018] (1) The method of the present invention for preparing the porous composite material M-COPs based on the Mannich reaction for synthesizing benzoxazine bridges is simple and efficient, using 1,4-dioxane as a solvent and without the need for a catalyst, thereby improving the material properties and reducing the preparation cost.
[0019] (2) The M-COPs prepared by the present invention produce a good photothermal conversion effect through 638nm wavelength laser irradiation, and can also catalyze oxygen and convert it into singlet oxygen, thereby achieving a synergistic antibacterial effect. It is worth noting that the inhibition rate of M-COPs against Gram-negative bacteria is higher than that against Gram-positive bacteria, and the inhibition rate of Gram-negative bacteria can be improved.
[0020] (3) The M-COPs prepared by the present invention have high biocompatibility, little effect on the cell viability of 3T3 cells, and a lysis rate of blood cells lower than 5%, which can promote wound healing, which is beneficial to its application in the biological field. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 :Hydrogen spectrum of 5,10,15,20-tetrakis(4-aminophenyl)-porphyrin;
[0022] Figure 2 :a) Infrared spectra of TAPP and M-COPs; b) Solid-state carbon spectra of M-COPs 13 C NMR; c) X-ray diffraction pattern of M-COPs; d) low-temperature N2 absorption isotherm at 77 K; e) pore size distribution curve of M-COPs; f) thermogravimetric curve of M-COPs;
[0023] Figure 3 : SEM and TEM of M-COPs: a) SEM of M-COPs at 5µm scale; b) SEM of M-COPs at 500nm scale; c) SEM of M-COPs at different angles at 500nm scale; d) TEM of M-COPs at 500nm scale; e) TEM of M-COPs at 200nm scale; f) TEM of M-COPs at 50nm scale; g) TEM of M-COPs at 50nm scale; h) HRTEM of M-COPs at 10nm scale; i) HRTEM of M-COPs at 5nm scale;
[0024] Figure 4 : Element distribution diagram of M-COPs;
[0025] Figure 5 : a) at 1.5 W / cm 2 Concentration-dependent photothermal effect of M-COPs under 638 nm laser irradiation; b) concentration-dependent photothermal effect of M-COPs under 638 nm laser irradiation at 0.5, 1.0, 1.2 and 1.5 W / cm 2 Laser power-dependent photothermal effect of M-COPs under 638 nm laser irradiation; c) Thermal imaging of the heating process of M-COPs (100 μg / mL) within 10 min; d) 638 nm laser at 1.5 W / cm 2 Temperature variation curve of M-COPs (100 μg / mL) after 5 times of photocooling under 638 nm laser (1.5 W / cm 2 ) Temperature curve of freshly prepared M-COPs aqueous suspension in water after 30 days of incubation under irradiation;
[0026] Figure 6 :a) Pure DPBF group under red light (λ = 638 nm, 1.5 W / cm 2 ) UV-visible spectra of the M-COPs group under red light (λ = 638 nm, 1.5 W / cm 2c) UV-visible spectra of the M-COPs group under red light (λ = 638 nm, 1.5 W / cm 2 d) UV-visible spectra of M-COPs under red light (λ = 638 nm, 1.5 W / cm 2 ) Attenuation rate of induced DPBF under irradiation (%);
[0027] Figure 7 : M-COPs with different concentrations were illuminated by red light (λ = 638 nm, 1.5 W / cm 2 ) E. coli culture images irradiated for 0, 5, and 10 minutes respectively;
[0028] Figure 8 :a) The plate counting method was used to measure the activity (%) of E. coli after red light treatment with different concentrations of M-COPs; b) The corresponding bacterial activity after treatment in different groups;
[0029] Fig. 9 : Fluorescence images of E. coli incubated with live / dead stains in PBS and M-COPs with and without laser treatment, respectively, and bacteria co-stained with SYTO-9 and PI (concentration: M-COPs = 100 μg / mL; scale bar = 200 μm, λ = 1.5 W / cm 2 , 10 minutes) wherein Figure a) represents the PBS group (control group), Figure b) represents the no-light group, and Figure c) represents the light group;
[0030] Fig.10 : TEM images of E. coli cultured in a) PBS (control), b) without illumination, and c) with illumination. The red tip represents the location of damage (concentration: M-COPs = 100 μg / mL; scale bar = 2 μm, λ = 1.5 W / cm 2 , 10 minutes);
[0031] Fig.11 : Hemolysis experiment of M-COPs: Hemolysis rate of M-COPs with different concentrations (n=3, error bars indicate standard deviation);
[0032] Fig.12 : Cytotoxicity experiment of M-COPs: Bacterial viability (%) after co-culture of 3T3 cells with different concentrations of M-COPs (n=3, error bars represent standard deviation);
[0033] Fig.13 : Representative photos of back wounds of mice infected with E. coli at each time point for each group of treatment;
[0034] Fig.14 : a) Changes in mouse body weight during treatment (n=5, error bars indicate standard deviation, *p<0.05, **p<0.01, ***p<0.001); b) Area diagram of wound healing in the three groups after treatment;
[0035] Fig.15 : Skin staining results: Day 9 of wound healing process; a) H&E staining images of wound tissues of each group, b) Masson staining images of wound tissues of each group (scale bar is 200 μm);
[0036] Fig.16 : Organ staining results;
[0037] Fig.17 : Results of routine blood tests on the 9th day of treatment in each group, data are expressed as mean ± standard error (n = 3); a) white blood cell (WBC) test results; b) red blood cell (RBC) test results; c) hematocrit (HCT) test results; d) mean hematocrit (MCV) test results; e) mean hemoglobin (MCH) test results; f) mean hemoglobin concentration (MCHC) test results; g) hemoglobin (HGB) test results; h) platelet (PLT) test results;
[0038] Fig.18 : A preparation route for the synthesis of benzoxazine-bridged porous composites based on the Mannich reaction. DETAILED DESCRIPTION
[0039] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0040] As introduced in the background technology section, although the existing porphyrin antibacterial materials can exert good photothermal effects, the preparation process of porphyrin-containing multipolymer antibacterial materials is complicated and takes a long time; and the inhibition rate against Gram-positive bacteria is higher than that against Gram-negative bacteria.
[0041] Based on this, the purpose of the present invention is to provide a porous composite material based on the Mannich reaction to synthesize benzoxazine bridges and its preparation method and application. The present invention uses hydroquinone, porphyrin and formaldehyde as structural units and adopts a one-pot method for preparation. Fig.18As shown, the present invention uses a cost-effective and simple Mannich reaction to prepare heterocyclic bridged porous material antibacterial agents. Formaldehyde is copolymerized with aromatic polyhydroxy and polyamino monomers under catalyst-free conditions. This simple and efficient synthesis method can produce a variety of novel COPs with new structures, and can also achieve large-scale preparation. In addition, COPs containing porphyrin units show impressive antibacterial properties in photothermal treatment. They can inhibit Gram-negative bacteria well, and this performance may be derived from their unique structure (benzoxazine ring, etc.). Therefore, the present invention provides a promising route for the preparation of benzoxazine bridged COPs.
[0042] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments.
[0043] Description: The reaction of the present invention is actually a polymerization reaction of hydroquinone, 5,10,15,20-tetrakis(4-aminophenyl)-porphyrin and formaldehyde. However, since formaldehyde is a gas and a toxic gas, the present invention uses paraformaldehyde instead of formaldehyde in the synthesis. Paraformaldehyde is a solid and is more suitable for synthesis reactions than toxic gases. Paraformaldehyde can gradually decompose formaldehyde under the reaction conditions of the present invention, and then formaldehyde participates in the reaction, which neither pollutes the environment nor harms human health. Under the solvent and heating temperature of the present invention, paraformaldehyde can quickly decompose formaldehyde. The reaction time of the present invention includes the decomposition time of paraformaldehyde. If formaldehyde gas is directly involved in the reaction, the reaction time will be further shortened. Calculated based on the molecular weight of paraformaldehyde of 90, the molar weight of 3.6g of paraformaldehyde is 40mmol, and 120mmol of formaldehyde can be released by complete decomposition. Therefore, in the embodiment, paraformaldehyde is added in excess until the two monomers of hydroquinone and 5,10,15,20-tetrakis(4-aminophenyl)-porphyrin are completely reacted.
[0044] Paraformaldehyde was purchased from Tianjin Guangfu Fine Chemical Co., Ltd.
[0045] The test materials used in the examples of the present invention are all conventional test materials in the art and can be purchased through commercial channels.
[0046] Example
[0047] (1) Synthesis of 5,10,15,20-tetrakis(4-aminophenyl)porphyrin (TAPP): p-nitrobenzaldehyde (11.3 g, 75 mmol), acetic anhydride (14 mL, 151 mmol) and propionic acid (200 mL) were mixed in a 500 mL flask and heated to 140 °C. Pyrrole (5.2 mL, 75 mmol) was then added. The mixture was refluxed for 30 min and then the heating was stopped. The mixture was cooled to room temperature and filtered to obtain a precipitate. The filtrate was washed with N,N-dimethylformamide and hot water until colorless and dried to obtain 5,10,15,20-tetrakis(4-nitrophenyl)porphyrin (TNPP, 1.21 g, yield: 24%).
[0048] 5,10,15,20-tetrakis(4-nitrophenyl)porphyrin (0.1 g, 25 mmol), sodium sulfide nonahydrate (0.604 g, 2.5 mmol) and ammonium chloride (0.06 g, 0.1 mmol) were added to a 100 mL three-necked flask. N,N-dimethylformamide (6 mL) and distilled water (0.2 mL) were added under argon protection. The temperature was raised to 90 °C and stirred for 3 hours, then cooled to 80 °C and maintained, and then 20 mL of distilled water was slowly added dropwise (20-40 drops / min). After the addition was completed, the mixture was cooled to room temperature, filtered and washed with distilled water until the filtrate was colorless and neutral, and dried in vacuo at room temperature to obtain a blue-purple solid, namely 5,10,15,20-tetrakis(4-aminophenyl)-porphyrin (TAPP), with a yield of 94%. 1 H NMR: 4.03 (s, 8H), 7.07 (d, 8H); 7.99 (d, 8H); 8.90 (s, 8H), the hydrogen spectrum of TAPP is shown in Figure 1 .
[0049] (2) Preparation of M-COPs: Add hydroquinone (2.2 g, 20 mmol), paraformaldehyde (3.6 g) and 5,10,15,20-tetrakis(4-aminophenyl)-porphyrin (3.37 g, 5 mmol) into a 100 mL two-necked round-bottom flask, and then inject 70 mL of 1,4-dioxane. Heat it to 100 °C for 6 h, and then cool it to room temperature. After filtering, wash it with distilled water, methanol, tetrahydrofuran and dichloromethane in sequence until the filtrate is colorless. Then dry it in a vacuum drying oven at 80 °C for 24 h to obtain M-COPs. The synthetic route of M-COPs is as follows: Fig.18 shown.
[0050] Characterization:
[0051] (1) Determination of infrared spectrum of catalyst: The structure of the catalyst was determined by infrared spectrum. 3 mg of 5,10,15,20-tetrakis(4-aminophenyl)porphyrin (TAPP), M-COPs and dried potassium bromide powder were ground in a mortar and kept dry at all times. Then, the mixture was placed in a tablet pressing mold to form a transparent, crack-free tablet. The tablet was placed in an infrared spectrum scanner at 500-400 cm -2 Scan 36 times within the range.
[0052] Fourier transform infrared spectroscopy (FT-IR) was used to verify the construction of M-COPs. Figure 2 As shown in a), the FT-IR of M-COPs combines the properties of TAPP and hydroquinone, and has characteristic vibration peaks attributed to the benzoxazine ring in addition to the characteristic vibrations of the reactive monomers. -1 and 1060 cm -1 The new absorption peak at 1250 cm-1 is from the oxazine ring (COC -1 The asymmetric stretching vibration peak at 1060 cm-1 and the COC peak at 1060 cm-1 -1 Compared with the porphyrin monomer, the 965 cm -1 The M-COP peak at -1 ) changes, among which 938 cm -1 The peak at is caused by the out-of-plane CH bending of the benzene ring to which the oxazine ring is connected (this peak is a characteristic absorption peak of the porphyrin ring). These results prove that a stable M-COPs complex has been formed.
[0053] (2) Through solid state 13 C-NMR further verified the carbon skeleton structure of M-COPs, such as Figure 2 As shown in Figure b), the presence of the benzoxazine ring can be clearly observed. The characteristic carbon atom resonances of Ar-CH2-N- and -O-CH2-N are located at 51.8 ppm and 87.2 ppm, respectively. In addition, the characteristic peaks at chemical shifts of 111.8 ppm and 120.1 ppm are attributed to the carbon of the pyrrole structure in the porphyrin ring, and 131.1 ppm and 144.8 ppm are the signal peaks of the benzene ring in the porphyrin ring, all of which prove the feasibility of the Mannich reaction for the targeted preparation of COP.
[0054] (3) The crystal morphology of M-COPs was understood through X-ray diffraction patterns. Figure 2 c) As shown, the peaks at 21.48° and 42° correspond to the benzoxazine structure.
[0055] (4) The pore distribution of M-COPs composite materials was understood through N2 adsorption-desorption curves and pore size distribution curves. Figure 2 d) - Figure 2 e) shows that the low-temperature N2 adsorption / desorption isotherm of M-COPs shows that the nitrogen adsorption-desorption curve of M-COPs is a type III isotherm, which is a typical feature of the mesopore-micropore coexistence curve. The curve shows an obvious hysteresis loop, which is attributed to the existence of mesopores in M-COPs. The surface area of M-COPs is calculated to be 49.9 m 2 ·g −1 The total pore volume is 0.117m 3 ·g −1 .
[0056] (5) The thermal stability of M-COPs composites was investigated by thermogravimetric analysis. Figure 2 As shown in f), M-COPs have strong thermal stability, which decreases at 180 °C, which is attributed to the cleavage ring opening of the oxazine ring.
[0057] (6) M-COPs were adhered to a mica substrate with conductive glue and sprayed with gold, and then the sample morphology was observed under SEM. The ultrasonically dispersed M-COPs methanol dispersion was dripped onto a copper mesh, and the observation sample was obtained after air drying. The sample was placed in a TEM to observe the sample morphology and take pictures, and the sample element analysis diagram and the atomic content table of various elements were derived.
[0058] The morphology of the M-COPs composites was observed by SEM. Figure 3 a) - Figure 3 c) shows the morphology of M-COPs at 5 μm and 500 nm. It can be seen that the bulk structure of M-COPs is composed of spherical particles (less than 200 nm). Consistent with the SEM results, Figure 3 d) - Figure 3 g) TEM shows that M-COPs are composed of spherical nanoparticles, and from the contrast between light and dark, it is found that there are mesopores in M-COPs. Figure 3 h) - Figure 3 As shown in i), the existence of micropores in M-COPs can be proved by bright field and dark field contrast. Figure 4 The element distribution of M-COPs is shown, and it can be seen that the C, N, and O elements are evenly distributed.
[0059] (7) Photothermal properties of M-COPs composites: The photothermal properties of M-COPs composites were investigated by changing the concentration of M-COPs aqueous dispersion (20, 40, 60, 80, and 100 μg / mL) or the power density of the laser (0.5, 1.0, 1.2, and 1.5 W / cm 2), the photothermal conversion performance of M-COPs was studied in detail. The preparation method of M-COPs aqueous dispersions with different concentrations is as follows: weigh 10 mg of M-COPs and fully disperse them in 1 mL of distilled water using an ultrasonic instrument to prepare a 10 mg / mL mother solution, then draw 2, 4, 6, 8 and 10 μL from the mother solution and add them to 998, 996, 994, 992 and 990 μL of distilled water, respectively, and finally prepare 20, 40, 60, 80 and 100 μg / mL of M-COPs aqueous dispersions.
[0060] Under laser irradiation (λ = 638 nm, 1.5 W / cm 2 , 10min), the temperature rise behavior of M-COPs with different concentrations was studied. Figure 5 a) - Figure 5 As shown in b), M-COPs exhibit a concentration- and power-dependent photothermal conversion capability, and its temperature increases significantly with the increase of M-COPs concentration and power. Figure 5 c) The temperature image obtained by the thermal imager can also intuitively reflect the concentration-dependent temperature rise behavior, which indicates that M-COPs have the ability to efficiently convert light energy into heat energy. Figure 5 d) shows the estimated photothermal stability of M-COPs through five consecutive laser on / off cycles. It can be clearly seen that the M-COPs exhibited an efficient photothermal response with almost no temperature fluctuation after five repeated on / off cycles, which is quite important for practical applications.
[0061] In addition, the photothermal conversion efficiency calculation formula is calculated with reference to the photothermal conversion efficiency formula in the "A Photothermal-Fenton-like Reaction Artificial Nanozyme and Its Preparation Method and Application" disclosed in application number CN202310175497.X, and the photothermal conversion efficiency (η) of M-COPs is 71.4%; Figure 5 e) The negative natural logarithm of the cooling time and temperature representing the M-COP, showing the τS and θ values in the light-to-thermal conversion efficiency calculation formula.
[0062] The meaning of each element in the light-to-heat conversion efficiency formula is: "h" is the heat transfer coefficient; S is the surface area of the container; "T max " is the equilibrium temperature after 10 minutes of irradiation (70.4°C); "T surr " is the ambient temperature during the experiment (23.9°C);" dis " is the heat dissipation of the test unit (25.03 mW); "I" represents the 638 nm laser power (1.5 W / cm 2 ). "A638" is the absorbance of M-COPs aqueous solution at 638 nm (0.6552).
[0063] Figure 5 f) shows the effect of 638 nm laser (1.5 W / cm 2 ) under irradiation, the temperature curve of M-COPs aqueous dispersion after incubation in water for 30 days shows that the temperature remains almost unchanged after being placed in water for a long time, and there is no obvious effect on the photothermal effect, indicating that the composite material has strong stability.
[0064] (8) Photodynamic performance of M-COPs: The photodynamic performance of M-COPs was investigated under 638 nm laser (1.5 W / cm 2 The photodynamic properties of the film under irradiation were studied.
[0065] 1, 3-Diphenylisobenzofuran (DPBF) was used as the photodynamic probe, 30 μg / mL DPBF dimethyl sulfoxide solution was used as the pure DPBF group, and 50 μg / mL and 100 μg / mL M-COPs dimethyl sulfoxide dispersions were used as the M-COPs group. 50μg / mL and 100μg / mL M-COPs dimethyl sulfoxide dispersions were prepared by mixing DPBF and M-COPs and dissolving them in dimethyl sulfoxide. The specific preparation method is as follows: weigh 1 mg of M-COPs and fully disperse it in 1 mL of dimethyl sulfoxide using an ultrasonic instrument to prepare a 1 mg / mL M-COPs mother solution. 50μL and 100μL of the M-COPs mother solution were respectively drawn into 950 and 900μL of DMSO to prepare 50μg / mL and 100μg / mL M-COPs dimethyl sulfoxide dispersions; 50μL of DPBF mother solution was added to the above dispersions to obtain M-COPs groups (50μg / mL and 100μg / mL). The singlet oxygen ( 1 O2). The more singlet oxygen is produced, the more DPBF is consumed. On this basis, the singlet oxygen produced by the M-COPs group and the pure DPBF group was determined.
[0066] like Figure 6 a) - Figure 6 c), where the pure DPBF group is the control group, with only the DPBF probe present. Except for the fact that the absorbance of the pure DPBF group hardly changed, the UV-visible absorption intensity of the M-COPs group at ~416nm showed a significant downward trend with the increase of laser irradiation time, indicating that DPBF is continuously consumed under light. For example, after 10 minutes of 638nm laser irradiation, the decrease rate of the 100μg / mL M-COPs group reached 51.04%, while that of the pure DPBF group was only 4.14%. From the curve of absorption intensity changing with time Figure 6 d) can more intuitively reflect the performance difference. Such results verify that M-COPs can generate photodynamic energy under laser excitation. 1O2.
[0067] Test Example 1: In vitro antibacterial test
[0068] (1) Bacterial culture: This experiment used Escherichia coli to complete the following experiments. The specific culture method of the second-generation bacteria is as follows: first, thaw the frozen Escherichia coli bacteria at 37°C, take 100 µL of the bacterial solution in a shaking tube containing 5 mL of liquid culture medium, place it in a constant temperature shaker (110 rpm, 37°C) and culture it for 12 hours, take 100 µL of the cultured bacterial solution and place it in a 2 mL EP tube containing 900 µL of liquid culture medium, and then dilute it according to the gradient method of 10 -2 Dilute 5-10 tubes, take 100 µL of the bacterial solution from each tube, use a spreading stick to evenly spread it on a culture dish containing solid culture medium, incubate at 37°C for 24 hours, observe the clone morphology and colony count, and take the culture dish with about 1000 colonies as the first generation of bacteria. Use a bacteria picking stick to pick out a colony from the first generation of bacteria and add it to a shaking tube containing 5 mL of liquid culture medium. Cultivate it according to the method of culturing first generation bacteria to obtain a culture dish with about 1000 colonies as the second generation of bacteria. Bacterial solution ( E. coli ) is a liquid culture medium. The specific preparation method is to take 5g of LB broth, disperse it in 200mL of distilled water, and then sterilize it by high pressure sterilization to obtain a bacterial liquid culture medium. The specific preparation method of the solid culture medium is to take 5g of LB broth and 3g of agar, disperse them in 200mL of distilled water, and then sterilize them by high pressure sterilization to obtain a solid culture medium.
[0069] (2) Determination of the antibacterial activity of M-COPs by plate counting method: After testing the performance of M-COPs on PTT and PDT, it can be concluded that M-COPs have certain antibacterial potential. The plate counting method was used to study the laser irradiation-induced antibacterial ability of M-COPs. The specific preparation method of the bacterial dispersion of different concentrations of M-COPs groups is as follows: take 2 mg of M-COPs powder, fully disperse it in 1 mL PBS, and prepare a 2 mg / mL M-COPs stock solution. Add 100 µL of 10 mL PBS to each of the 6 2 mL EP tubes. 8 CFU mL -1 850, 860, 870, 880, 890 and 900 μL of PBS were added, and then 50, 40, 30, 20, 10 and 0 μL of 2 mg / mL M-COPs stock solution were added to prepare 0, 20, 40, 60, 80 and 100 μg / mL M-COPs and 10 8 CFU mL -1The PBS dispersion was the M-COPs solution. Then, the M-COPs solution with different concentrations was irradiated with laser (laser parameters: λ = 638 nm, 1.5 W / cm 2 , 10min), and the M-COPs solutions of different concentrations were placed in a constant temperature shaker (110rpm, 37℃) for 12h, and then the cultured bacterial solution was gradiently diluted 10 5 Transfer 100 μL of the blown bacterial solution to the solid culture medium and spread it evenly. Incubate at 37°C for 24 hours to observe the morphology of the clones. Count the colonies and compare the bacterial activity of each group. Figure 7-8 As shown, the number of surviving bacteria treated with M-COPs was significantly increased under laser irradiation (638 nm, 1.5 W / cm 2 , 0, 5 and 10 min). The antibacterial effect increased significantly with the increase of M-COPs concentration. The bactericidal ability of M-COPs became stronger with the increase of M-COPs solution concentration and laser irradiation time, and the bactericidal ability of M-COPs was stronger against Escherichia coli ( E. coli ) has greatly enhanced its bactericidal properties. M-COPs can achieve an antibacterial rate of nearly 100% against Escherichia coli at an extremely low concentration (100 μg / mL), and the antibacterial effect of M-COPs on Escherichia coli is significantly better than that of other porphyrin-based COPs. In short, M-COPs has good synergistic PTT and PDT antibacterial ability and can be used as a spectrum antibacterial agent with potential antibacterial ability to replace antibiotics.
[0070] Test Example 2: Bacterial live / dead staining test:
[0071] SYTO-9 and PI are used to distinguish between live and dead microbial cells. SYTO-9 penetrates all bacterial membranes (intact and damaged), thus marking the bacteria green. On the other hand, PI only penetrates the damaged bacterial membranes, marking the bacteria red while reducing the green color of SYTO-9.
[0072] The bacterial solutions of the PBS group, M-COPs group (100 μg / mL), and M-COPs (100 μg / mL) + laser group (i.e., control group, no-light group, and light group) were prepared according to the method in Experimental Example 1; the laser parameters were: λ = 638 nm, 1.5 W / cm 2 , 10 min. Then, 100 µL of bacterial suspension from each group was mixed with 20 µL of SYTO-9 (1.0×10 -3 M) and 20 µL PI (1.5 × 10 -3M) and co-incubation was performed for 15 min in the dark at 37°C. After staining, each treatment was centrifuged in PBS to remove excess SYTO-9 and PI. The bacteria were then resuspended in 50 µL PBS and placed on the surface of the slide. Images of E. coli were then captured using a fluorescent inverted microscope.
[0073] from Fig. 9 It can be seen that the results of live / dead staining are consistent with the results of the aforementioned co-culture experiment. E. coli under different treatments present different fluorescence signals. The bacteria treated with the PBS group only present strong green fluorescence. However, for the bacteria under the treatment of other groups, the group irradiated with laser presents much stronger red fluorescence than the single material. The M-COPs+laser group (illumination group) presents the most prominent sterilization effect, in which almost all E. coli are marked in red. For the M-COPs group (no illumination group), only a few E. coli are stained red. This further proves the superiority of M-COPs in synergizing PTT and PDT antibacterial.
[0074] Test Example 3: Bacterial transmission electron microscopy:
[0075] The bacterial solutions of the PBS group, M-COPs group (100 μg / mL), and M-COPs (100 μg / mL) + laser group (i.e., control group, no-light group, and light group) were prepared according to the method in Experimental Example 1; the laser parameters were: λ = 638 nm, 1.5 W / cm 2 , 10min. Afterwards, take the bacterial culture ( E. coli ) was fixed in 2.5wt% glutaraldehyde solution (4 °C, 2h), washed three times with PBS, embedded in agar and blocked. Then, the bacteria were treated with ethanol solution (30 wt%, 50 wt%, 70 wt%, 90 wt%, 95 wt% and 100 wt%) at room temperature for 10 min to dehydrate the bacteria, followed by acetone treatment at room temperature for 3 h, embedded with embedding medium (epoxy resin) gradient infiltration (immersion in acetone and epoxy resin mass ratio of 3:1, 1:1, 1:3 for 1 hour, and finally pure epoxy resin overnight) for negative staining, and sectioned on nickel grids. The nickel grid was placed under TEM for observation to capture the morphology of bacteria.
[0076] TEM was used to observe the integrity of bacterial membranes in different groups. Fig.10As shown in the figure, in the PBS group (control group), the bacterial membrane of Escherichia coli was intact, indicating that the viability of the bacteria was not affected by light. The bacterial membrane under the treatment of M-COPs group (no light group) was weakly damaged, but the degree of damage was significantly less than that of the M-COPs+laser group (light group). Similar to the live / dead staining results, the bacterial membranes of the other groups were also damaged to varying degrees. M-COPs+laser caused the most serious damage to its bacterial membrane, and a large amount of bacterial contents flowed out. Therefore, the M-COPs composite material with synergistic PDT and PTT antibacterial ability has great application potential as a broad-spectrum antibacterial agent without antibiotics, which can effectively kill bacteria.
[0077] Test Example 4: In vitro biocompatibility test:
[0078] (1) Hemolysis test
[0079] Fresh blood was collected from BALB / c female mice (purchased from Jinan Pengyue Experimental Animal Breeding Co., Ltd.). Red blood cells were collected by centrifugation at 1500rpm for 20min and then washed three times with PBS. Red blood cells (4% w / w) were then incubated with M-COPs (0~150 µg / mL) at a ratio of 1:9 (v / v) at 37°C for 3h and then centrifuged at 12000 rpm for 20min. Then, 100μL of supernatant from each group was placed in a 96-well plate, and the absorbance of each group was measured at 570nm using a microplate reader. Distilled water was used as a positive control and PBS was used as a negative control. The amount of hemolysis was calculated using the following formula 4:
[0080] Hemolysis volume (%) = (A-An) / (Ap-An) × 100%;
[0081] Where "A" is the absorbance obtained by taking the supernatant after adding M-COPs to erythrocytes. "An" is the absorbance obtained by taking the supernatant after adding PBS to erythrocytes (negative control). "Ap" is the absorbance obtained by taking the supernatant after adding distilled water to erythrocytes (positive control).
[0082] like Fig.11 As shown, M-COPs showed only a small amount (less than 2%) or no hemolytic activity within the concentration range where they showed antimicrobial activity. The hemolysis rate of M-COPs varied with the concentration of M-COPs, increasing from 1.14±0.04% to 1.86±0.04% as the concentration increased from 30 to 150 μg / mL. This indicates that M-COPs have good blood compatibility and have no or negligible damage to the red blood cell membrane.
[0083] (2) Cytotoxicity assay
[0084] 3T3 cells (German Cell Bank (DSMZ): ACC 305) were cultured at 5 × 10 cells per well in a 96-well plate. 3 Cells were seeded at a density of 100 cells per well, 180 µL of cells per well, and 200 µL of PBS was added to the surrounding duplicate wells for liquid sealing to prevent excessive evaporation. After incubation for 24 h, 20 µL of M-COPs at different concentrations (30-150 μg / mL) were added and incubated for 72 h. Then 20 µL of MTT (4 mg / mL) solution was added to each well and incubated in the incubator for 4 h. After 4 h, the supernatant was aspirated and 150 µL of dimethyl sulfoxide was added to dissolve MTT (tetramethylthiazolyl blue). After dissolving on a shaker for 10 min, the absorbance of the 96-well plate was measured at 570 nm using a microplate reader. Each set of experiments was repeated three times.
[0085] At the same time, in order to further study the adverse damage of the material itself to normal cells, the cytotoxicity test of M-COPs on 3T3 was carried out. Fig.12 The cell viability of 3T3 cells cultured for 3 days with different concentrations of M-COPs (30-150 μg / mL) is shown. It can be clearly seen that the relative cell viability gradually increased with the decrease in material concentration, and its value can be maintained at more than 80% at all experimental concentrations, indicating no toxicity to 3T3 cells. All these results confirm that M-COPs with good biocompatibility are selective agents for bacteria.
[0086] Test Example 5:
[0087] (1) In vivo wound healing experiment:
[0088] To evaluate the role of M-COPs in wound healing, a dorsal cortical injury wound model of BALB / c mice infected with Escherichia coli was established. For comparison, the in vivo antibacterial capacity of the control, no-light, and light groups was also estimated.
[0089] Five-week-old female BALB / c mice (Jinan Pengyue Experimental Animal Breeding Co., Ltd.) (n = 6 per group, 22-25 g) were used and divided into 4 groups (6 mice per group), namely, blank group, control group, no-light group, and light group;
[0090] Blank group: mice were not treated with modeling and had no wounds.
[0091] Control group (PBS): After the wound model was established, the wound was treated with PBS, 100 µL;
[0092] No-light group: After the wound model was established, the wound was treated with 100 µg / mL M-COPs, 100 µL;
[0093] Irradiation group: After the wound model was established, the wound was treated with 100 µg / mL M-COPs + laser, and the laser parameters were λ=638nm, 1.5W / cm 2 , 10min; 100 µL.
[0094] The specific modeling method is as follows: after disinfection with ethanol solution (75%), the dorsal hair of each mouse was shaved before surgery to form a wound of d = 5 mm, and then Escherichia coli (1×10 6 CFU / mL) for 24 h. The infected wounds were then treated with each group, and the wound surface was photographed on days 0, 1, 3, 5, 7, and 9, while the weight of the mice was monitored. Changes in wound size were measured using an image analysis program (Image.J, National Institutes of Health).
[0095] The specific experimental method is: one day after the establishment of the E. coli-infected BALB / c mouse dorsal cortical damaged wound model, each group of wounds was treated with the above dosage, which is the wound treatment. Day 0 to day 1 is the modeling time, and the damaged wounds are infected with E. coli. In addition, the wounds of the mice were photographed and recorded on days 1, 3, 5, 7 and 9. Fig.13 As shown, day 1 shows the photograph of the back wound of the mouse one day after treatment. It can be seen that all the wounds showed the characteristics of bacterial infection, and the wound contraction rate of all groups was almost the same. Compared with the swelling in the no-light group and the control group, the wounds in the light group further shrank as the treatment time prolonged. In contrast, the treated wounds in the light group healed well on the 9th day, and the wounds treated in the laser irradiation group healed much better than those in the no-light group. All these results indicate that laser irradiation of M-COPs in the light group can not only significantly reduce bacterial invasion, but also accelerate wound contraction compared with the other groups. At the same time, the body weight of BALB / c mice was recorded every day for further comparison. As shown Fig.14 As shown in a), during the 9-day treatment, the mice in each group had no obvious behavioral abnormalities and no significant changes in body weight. Fig.14 The wound area overlay diagram in b) also clearly shows the wound healing status.
[0096] (2) In vivo biocompatibility study: tissue staining experiment (HE staining)
[0097] In order to further study the wound healing of mice in each group, hematoxylin and eosin (H&E) staining and Masson staining were used to evaluate the wound healing of mice in the wound healing test of experiment (1) of this experiment example. Fig.15 a) shows the H&E staining results of the three groups. Fig.15b) Masson staining results of the three groups. Histological analysis of wounds infected with E. coli showed that all groups had new capillaries and skin growth to varying degrees. The most intuitive thing is that the scab area of the wound in the light-exposed group was smaller than that in the non-light-exposed group, indicating that the healing speed of the M-COPs group after laser irradiation was significantly accelerated. The control group had the largest scab area, few new capillaries and skin, and a large number of inflammatory cells. Therefore, M-COPs can accelerate wound reconstruction more quickly after laser irradiation.
[0098] To investigate the in vivo biocompatibility of M-COPs, heart, liver, spleen, lung, and kidney of BALB / c mice were subjected to tissue sectioning and H&E staining. Fig.16 As shown, the results showed that there was no obvious inflammation and morphological damage in different organs of each group.
[0099] (3) Routine blood test
[0100] In order to investigate the in vivo biocompatibility of M-COPs, blood was drawn from the eyes of the above-mentioned BALB / c mice for routine blood tests. On day 9, 1-2 mL of blood samples were collected from the retinal arteries of the mice. 200 μL of each blood sample was taken for routine blood analysis, including the number of white blood cells, the number of red blood cells, hematocrit, mean hematocrit, mean corpuscular hemoglobin, mean hemoglobin concentration, hemoglobin, and platelet count. The results are shown in Table 1. Fig.17 As shown, no significant differences were found in the blood routine values among the groups.
[0101] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for synthesizing a benzoxazine-bridged porous composite material based on a Mannich reaction, characterized in that: The method is: Add polyhydroxyphenol, 5,10,15,20-tetrakis(4-aminophenyl)-porphyrin and formaldehyde to 1,4-dioxane, heat and stir, cool and filter to obtain a black solid, wash and dry to obtain a benzoxazine-bridged porous composite material; The polyhydroxyphenol is hydroquinone; The ratio of the added amounts of hydroquinone, 5,10,15,20-tetrakis(4-aminophenyl)porphyrin, formaldehyde and 1,4-dioxane is 20 mmol:5 mmol:80 mmol:70 mL; The heating and stirring temperature is 100° C., and the heating and stirring time is 4 to 8 hours.
2. The method according to claim 1, characterized in that The 5,10,15,20-tetrakis(4-aminophenyl)-porphyrin is prepared by the following method: (1) p-nitrobenzaldehyde, acetic anhydride and propionic acid are mixed and heated, and then pyrrole is added, refluxed, cooled to room temperature, filtered to obtain a precipitate, washed and dried to obtain 5,10,15,20-tetrakis(4-nitrophenyl)porphyrin; (2) Mix 5,10,15,20-tetrakis(4-nitrophenyl)porphyrin, sodium sulfide nonahydrate and ammonium chloride, add N,N-dimethylformamide and distilled water under argon protection to react, cool and add distilled water dropwise, and after the addition is complete, cool, filter, wash and dry to obtain a dark purple solid, which is 10,15,20-tetrakis(4-aminophenyl)porphyrin.
3. The benzoxazine-bridged porous composite material obtained by the method according to claim 1 or 2.
4. Use of the benzoxazine-bridged porous composite material according to claim 3 in the preparation of antibacterial drugs or in the preparation of products for improving the inhibition rate of Gram-negative bacteria.
Citation Information
Patent Citations
A photothermal-Fenton-like artificial nanozyme, its preparation method and application
CN115845086B
Multifunctional cationic covalent organic framework material and application thereof
CN116789980A
A porphyrin microporous composite material based on β-cyclodextrin terephthalaldehyde inclusion compound and its preparation method and application
CN117327210B
Specific porphyrin self-transport nano carrier material and preparation method thereof
CN112121166A
Preparation method of porphyrin-anthracene covalent organic framework capable of realizing continuous phototherapy
CN117487158A